Postharvest Quality and Shelf life of Garlic Bulb as Influenced by Storage Season, Soil Type and Different Compound Fertilizers - G, Diriba Shiferaw; Woldetsadik, Kebede; R, Nigussie Dechassa; Tabor, Getachew; Sharma, J J (Journal of Postharvest Technology, 2013)
The experiment was conducted twice during rainy (2011/12) and dry (2012/13) seasons at Debre Zeit Agricultural Research Centre, Ethiopia, to evaluate effects of pre-harvest fertilizer application, soil type and storage season on postharvest quality and storability of garlic bulb. The treatments comprised twelve different fertilizer types and doses i.e. control, recommended N and P (92 and 40 kg ha-1), three rates of Azofertil (100, 200 and 300 kgha-1), four rates of Basic (100, 200, 400 and 600 kgha-1) and three rates of D-coder (100, 200 and 400 kgha-1) evaluated in two soil types (Andosol and Vertisol) and replicated thrice using Complete Randomized Block Design. Two storage seasons (dry and Rainy) were used for bulbs storage. Significant variations in storability and quality of bulbs were recorded to the fertilizers, soil type and storage season. Higher rates of fertilizers improved storability and quality of bulb whereas higher weight and diameter losses were observed in bulbs from control plot and plots treated with lower levels of each fertilizer. Garlic grown on Andosol and subsequent storage during the rainy season recorded better bulb qualities with long storability. D-coder at the rates of 200 and 400 kgha-1, followed by Azofertil at 200 and 300 kgha-1, recorded higher percent of dry matter, total soluble solids and pungency of bulbs and lower percent in weight and diameter losses. Thus application of these fertilizers on Andosol is a better compromise for post harvest quality and shelf life of garlic bulbs under ambient storage conditions.